Analysis of the AHP-WP Method in the Decision Support System for the Assessment of Outstanding Students at ITEKES Bali - Komang Gde Hendra Kusuma Putra; I Made Candiasa; Gede Indrawan (Jurusan Teknik Informatika, 2022)
Purpose: This study aims to analyze and determine the effectiveness of the combination of decision-making methods in the selection of outstanding students using the Analytical Hierarchy Process (AHP) and Weighted Product (WP) methods.Design/methodology/approach: A quantitative approach is used to analyze the combination of AHP and WP methods in determining outstanding students. The ranking results were analyzed using Mean Absolute Percentage Error (MAPE).Findings/result: This research produces a combination analysis of the AHP and WP decision-making methods, so that it can be used for implementation into information systems.Originality/value/state of the art: The difference between this study and previous studies is the combination of methods used in this study. An analysis of the effect of several variables in increasing accuracy is also produced.